Development of carbon nanotube - Reinforced silk and cannabis fibers by an electrophoretic deposition method - Somjate Veingnon (2018)
Carbon nanotubes (CNTs) were deposited by electrophoretic deposition (EPD) on Bombyx mori (silk) and Cannabis sativa L. var. sativa (hemp) fibers to improve their mechanical properties. The CNTs were functionalized in mixed acids in order to introduce carboxylic acid groups on their surfaces. The tensile strength and strain at break point of both the modified fibers were approximately two times higher than those of the virgin natural fibers. The addition of small amounts of Mg(NO3)2.6H2O, (CH3COO)2Ni.4H2O significantly improved the deposition of the functionalized CNTs on the hemp fibers. © (2011) Trans Tech Publications.